The Great Mortgaging: Housing Finance, Crises, and Business Cycles - Òscar Jordà; Moritz Schularick; Alan M. Taylor (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper unveils a new resource for macroeconomic research: a long-run dataset covering disaggregated bank credit for 17 advanced economies since 1870. The new data show that the share of mortgages on banks' balance sheets doubled in the course of the 20th century, driven by a sharp rise of mortgage lending to households. Household debt to asset ratios have risen substantially in many countries. Financial stability risks have been increasingly linked to real estate lending booms which are typically followed by deeper recessions and slower recoveries. Housing finance has come to play a central role in the modern macroeconomy.
Keywords: C14; C38; C52; E32; E37; E44; E51; G01; G21; N10; N20; 330; leverage; recessions; mortgage lending; financial crises; business cycles; local projections